Pengaruh Model Paired Storytelling terhadap Keterampilan Berbicara pada Materi Menceritakan Kembali Isi Fabel di Kelas VII SMP Negeri 1 Tigabinanga - Juli Laurensia Br Ginting; Rosmaini Rosmaini (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research is motivated by the low speaking skills of students in retelling fable texts which are influenced by several factors. This study aims to determine the effect of the paired storytelling learning model on students' speaking skills in retelling fables in class VII of SMP Negeri 1 Tigabinanga. The method used in this study is an experimental method with a two-group posttest only design. The population in this study were all students of class VII of SMP Negeri 1 Tigabinanga totaling 210 people and the sample of this study was students of class VII 3 experimental class with a total of 31 students and VII 4 as a control class with a total of 30 students. The data analysis technique used in this study is quantitative data by testing the analysis requirements, homogeneity test, homogeneity, and hypothesis test. The results of the study in the experimental class obtained an average value of 82.90 in the good category, while the results of the study in the control class at an average value of 53.50 were in the very poor category. Based on the test of equality of average values, it is known that the experimental class has a higher value than the control class with a difference of 29.4%. Based on the t-test that has been carried out, the value at the significance level α = 0.05 is obtained, the value of the t-table provision is 1.67109 and the result of t count = 10.8110. Then the hypothesis t-test> t-test, namely 10.8110> 1.67109, so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. In terms of consistency, it can be concluded that learning by using the paired storytelling model has a positive and significant effect on the skills of telling the contents of fable texts of class VII students of SMP Negeri 1 Tigabinanga.